EFFECT OF SOWING DATE AND DEFOLIATION ON GROWTH AND YIELD OF SUNFLOWER (Helianthus annum L.) - Ayad T. Shaker (Mesopotamia Journal of Agriculture)
Field experiment on sunflower was conducted during the season 2006 at Al Rashidia field-Mosul city to determine the effect of sowing dates{ 27 March(S1), 20 April (S2) and 10 May (S3) } with leaves defoliation { non-defoliation(Dl),defoliated 4 (D2) and 8 (D3) leaves / plant } at stage pale yellow of back head. It used randomized complete block design as split-plot with three replications. The result showed that 27 March of date sowing had a significant superiority on leaf area, no. of seeds / head, wt. of 1000 seeds and oil yield, while defoliation of 4 or 8 leaves had exactly opposed effect except the leaf area. Higher oil and seed yield had reached at(S1), (S2) with (D1) interaction. However, linear relationship was seen between defoliation levels and yield reduction percentage.